Supportive psychological therapy can effectively treat post-stroke post-traumatic stress disorder at the early stage - Jiang, Che; Li, Zhensheng; Du, Chenggang; Zhang, Xiwu; Chen, Zhuang; Luo, Gaoquan; Wu, Xiaona; Wang, Jiajia; Cai, Yan; Zhao, Gang; Bai, Hongmin (Frontiers in Neuroscience, 2022)
Post-traumatic stress disorder (PTSD) can develop after stroke attacks, and its rate ranges from 4 to 37% in the stroke population. Suffering from PTSD not only decreases stroke patient’s quality of life, but also relates to their non-adherence of treatment. Since strokes often recur and progress, long-term medical management is especially important. However, previous studies generally focused on the epidemiological characteristics of post-stroke PTSD, while there are literally no studies on the psychological intervention. In our study, 170 patients with a first-ever stroke during the acute phase were recruited. They were randomized into Psycho-therapy group 1 and Control group 1, and were administered with preventive intervention for PTSD or routine health education, respectively. At 2-month follow-up, PTSD symptoms were evaluated. Participants who were diagnosed with post-stroke PTSD were further randomized into Psycho-therapy group 2 and Control group 2, and received supportive therapy or routine health counselling, respectively. At 6-month follow-up (one month after the therapy was completed), PTSD symptoms were re-evaluated. Our results showed that at 2-month, the PTSD incidence in our series was 11.69%, and the severity of stroke was the only risk factor for PTSD development. The preventive intervention was not superior to routine health education for PTSD prevention. At 6-month, results indicated the supportive therapy did have a fine effect in ameliorating symptoms for diagnosed PTSD patients, superior to routine health counseling. Thus, our study was the first to provide evidence that the supportive therapy was effective in treating post-stroke PTSD early after its diagnosis. (This clinical trial was preregistered on www.chictr.org.cn (ChiCTR2100048411).